2006
DOI: 10.1007/s00330-006-0450-8
|View full text |Cite
|
Sign up to set email alerts
|

Teleradiology applications with DICOM-e-mail

Abstract: For the connection of several partners to a Dicom-e-mail based teleradiology network concepts were developed to allow the integration of different teleradiology applications. The organisational and technical needs for such an integration were analysed. More than 60 institutions including 23 hospitals in the Rhein-Neckar-Region, Germany were connected. The needed functionality was grouped in six teleradiology applications (emergency consultation, tele-guided examinations, expert consultations, cooperative work,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 12 publications
0
11
0
3
Order By: Relevance
“…There is also a demand for further harmonisation of legislation regarding the processing of health data in cross-border healthcare services: a European directive is required to further guarantee the safety of patients. The ESR has published several documents in which they have expressed their vision and concerns about teleradiology and have also provided guidelines and recommendations for the development and use of teleradiology services within the EU [1, 32–34]. …”
Section: Discussionmentioning
confidence: 99%
“…There is also a demand for further harmonisation of legislation regarding the processing of health data in cross-border healthcare services: a European directive is required to further guarantee the safety of patients. The ESR has published several documents in which they have expressed their vision and concerns about teleradiology and have also provided guidelines and recommendations for the development and use of teleradiology services within the EU [1, 32–34]. …”
Section: Discussionmentioning
confidence: 99%
“…In our study, it was revealed that 41.6% of the participants did not use teleradi-ology systems and we consider that the main reasons and lack of financial support and technical problems. 7,[10][11][12] It was also found that DICOM was the most commonly transmitted format (63.3%), as revealed in the European and Swiss survey. 7,10 In our study, the most common reason for the use of teleradiology outsourcing was revealed as secondary readings and expert consultation, and the most common disadvantages were revealed as insufficient integration of clinical history and lack of contact with the radiologist.…”
Section: 7-9mentioning
confidence: 85%
“…7,[10][11][12] It was also found that DICOM was the most commonly transmitted format (63.3%), as revealed in the European and Swiss survey. 7,10 In our study, the most common reason for the use of teleradiology outsourcing was revealed as secondary readings and expert consultation, and the most common disadvantages were revealed as insufficient integration of clinical history and lack of contact with the radiologist. Of all the participants, 27% declared a lack of integration of clinical history, 27% stated a lack of contact, and 58.8% declared inaccurate clinical data leading to inadequate interpretation.…”
Section: 7-9mentioning
confidence: 85%
See 2 more Smart Citations